Kapasitas Resin Immobilized Photocatalyst Technology (RIPT) untuk Menurunkan Parameter Bod Limbah Cair Industri Tahu - Khusnul Khotimah Ayuningtiyas; Euis Nurul Hidayah; Aussie Amalia (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Tofu liquid waste contains organic material, namely BOD which is quite high, if it is directly discharged into water bodies, it will reduce the carrying capacity of the environment. This causes the carrying capacity of the environment to decrease and ecosystem performance to become unbalanced, so that further processing is needed, namely Resin Immobilized Photocatalyst Technology (RIPT). In this study, the BOD reduction process was carried out with resin, photocatalyst, and immobilization. The process of immobilizing the catalyst against the resin aims to expand the surface and maintain photocatalyst activity. The type of catalyst used is ZnO and TiO2. After obtaining the RIP (Resin Immobilized Photocatalyst), then the RIP was added to the wastewater and the BOD concentration in the tofu wastewater was calculated. The resin capacity is calculated with the aim of knowing the ability of the resin to reduce the concentration of BOD. From the research that has been done, it can be concluded that the highest resin capacity when using ZnO catalyst is 0.3159 g/L and 0.2806 g/L using TiO2. The effluent parameter concentration is directly proportional to the resin capacity. As the sampling time increases, the resin's ability decreases.